2014
DOI: 10.18052/www.scipress.com/ilns.25.18
|View full text |Cite
|
Sign up to set email alerts
|

Rural Farmers’ Perceptions, Knowledge and Management of Insect Pests of Fruit Vegetables in Ogbomoso Agricultural Zone of Nigeria

Abstract: Surveys were carried out in five local government areas of Ogbomoso Agricultural Zone Nigeria during planting season in 2010 to investigate rural farmers perceptions and management practices of insect pests of fruit vegetables. The survey involved 150 randomly selected farmers who were interviewed using structured questionnaire. Fruit vegetables planted by the farmers were okra, tomatoes, pepper and garden egg. Reasons given by farmers for cultivating fruit vegetables were significantly favored by age category… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
0
10
2
Order By: Relevance
“…Hornworm is the larval stage of the five-spotted hawk moth (Manduca quinquemaculata) of the family Sphingidae of Lepidoptera (Klass, 2012). Farmers' perception of insect type infesting fruit vegetables in Ogbomoso Agricultural Zone of Nigeria revealed similar findings that moth caterpillar is one of the serious pests damaging tomato fruits (Olaniran et al, 2014). Variegated cutworm (Peridroma saucia) was another pest that seriously attacked foliage of spinach and lettuce.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Hornworm is the larval stage of the five-spotted hawk moth (Manduca quinquemaculata) of the family Sphingidae of Lepidoptera (Klass, 2012). Farmers' perception of insect type infesting fruit vegetables in Ogbomoso Agricultural Zone of Nigeria revealed similar findings that moth caterpillar is one of the serious pests damaging tomato fruits (Olaniran et al, 2014). Variegated cutworm (Peridroma saucia) was another pest that seriously attacked foliage of spinach and lettuce.…”
Section: Discussionmentioning
confidence: 71%
“…Presence of aphids on tomato agrees with the findings of some researchers like Umeh et al (2002) who reported aphids as the most occurred insect pest attacking tomato in six states of Nigeria. Another survey by Olaniran et al (2014) in Ogbomoso Agricultural Zone of Nigeria confirmed the occurrence of caterpillars such as hornworm infesting tomato and some other fruit vegetables, and also identified these pests as the most damaging pests of fruit vegetables in Africa. The findings of the study have shown that aphid had the highest percentage of occurrence which was found attacking leaves of tomato and sweet pepper.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations